2016
DOI: 10.1080/1828051x.2016.1269300
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of feedingAspergillus awamoriand lactic acid bacteria on performance, egg traits, egg yolk cholesterol and fatty acid profile in laying hens

Abstract: This study was conducted to examine the effects of a combined supplementation of Aspergillus awamori (AA) and lactic acid bacteria (LAB) in feed on growth and egg quality. Hens (28-week old) were fed on a basal diet as control group; diets supplemented with 0.05% AA, 0.10% LAB, or a combination of AA and LAB (6 birds/group) for 6 weeks. The growth performance of the birds was improved by all the treatments. Synergistic effects of AA and LAB were observed on feed intake, egg production, total egg weight and fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
(52 reference statements)
7
37
0
Order By: Relevance
“…The possible mechanisms by which A. awamori exerts effect are: its superior ability to secrete enzymes able to degrade the non-starch polysaccharides (NSP) and fibre contents of OP, and its role as a probiotic. In addition, the ability to lower egg cholesterol levels had been previously reported for both OP (Hashish and Abd El-Samee, 2005;Saleh et al, 2017) and A. awamori (Imaizumi et al, 1992;Hara et al, 1999;Tang et al, 2015), and this coincides with the increasing demand for low-cholesterol or unsaturated fatty acids in eggs. Therefore, in this study, laying quails were selected as experimental subject to examine the effect of OP with or without A. awamori dietary inclusion on their productive performance, egg quality, and biochemical and antioxidant status.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…The possible mechanisms by which A. awamori exerts effect are: its superior ability to secrete enzymes able to degrade the non-starch polysaccharides (NSP) and fibre contents of OP, and its role as a probiotic. In addition, the ability to lower egg cholesterol levels had been previously reported for both OP (Hashish and Abd El-Samee, 2005;Saleh et al, 2017) and A. awamori (Imaizumi et al, 1992;Hara et al, 1999;Tang et al, 2015), and this coincides with the increasing demand for low-cholesterol or unsaturated fatty acids in eggs. Therefore, in this study, laying quails were selected as experimental subject to examine the effect of OP with or without A. awamori dietary inclusion on their productive performance, egg quality, and biochemical and antioxidant status.…”
Section: Introductionsupporting
confidence: 63%
“…These increment in EW and EN may be due to the residues of olive oil and its high contents of polyunsaturated fatty acids, mainly α-linoleic acid (March and MacMillan, 1990;Grobas et al, 1999Grobas et al, , 2001Güçlü et al, 2008). In addition, the eminent ability of A. awamori to produce cellulase and xylanase, and digest raw starches as well as soluble NSP (Saleh et al, 2017) found in the diet and OP, besides its role as probiotic, may enhance the utilization of OP and diet ingredients which in result improves quail productive performance. The previous aspects may be considered as explanations of the enhance-ment effect observed in the aforementioned groups.…”
Section: Productive Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The humate (humic, fulvic, ulmic, and humatomelanic acids) and probiotic together in the diets of laying hens during late laying period increased egg production and improved feed conversion efficiency (FCR) without any effect on egg quality (Yoruk et al, 2004). A mixture of additives containing both Aspergillus awamori and lactic acid bacteria had no effects on the performance of laying hens, but significantly increased unsaturated and reduced saturated fatty acid contents in the egg yolk (Saleh et al, 2017). Finally, dietary supplementation with selenium enriched yeast products could be more efficient in increasing selenium bioavailability of whole egg compared to the inorganic selenium sources (Chantiratikul et al, 2017).…”
Section: Introductionmentioning
confidence: 99%